(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The purpose of this study is to review some of the key research concepts related to metallurgical coke. As the research landscape for coke metallurgy is evolving, researchers are increasingly interested in the effects of the intrinsic properties of coal, coal preparation parameters, and the technological conditions of coke production on the quality of metallurgical coke. As part of this review, a specific protocol, content analysis and thematic coding of cases of the “Preferred Reporting Items for Systematic Review and Meta-Analyses” method were used to investigate the simultaneous effect of these two parameters on the quality of coke in selected journal articles. A review of 118 articles was conducted, including their abstract, introduction, methodology, and results. According to the results of this study, coal blends and coal particle sizes have a direct effect on the three sections of coke mechanical properties, coke texture, and coke reactive properties. Reviewing various articles has shown that the presence of fatty coals in smaller size distribution, combined with larger-sized weak coals, leads to the formation of a stronger structure in the produced coke. However, this does not guarantee an improvement in the coke reactivity parameters. On the other hand, increasing the blending ratio of coking coals in the final mixture for producing normal-sized coke (dimensions smaller than 3 millimetres) improves the coke reactivity parameters. Studies investigating coke structure have demonstrated that a cohesive mosaic structure in high-quality cokes results from well-distributed maceral blends of coking coals with optimal size distribution among other coals.